2010
DOI: 10.1021/ja105263q
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Anion Recognition Exhibited by a Halogen-Bonding Rotaxane Host System

Abstract: We report the first use of solution-phase halogen bonding to control and facilitate the assembly of an interlocked structure through the bromide anion-templated formation of a rotaxane based upon an iodotriazolium axle. The incorporation of a halogen atom into the rotaxane host cavity dramatically improves the anion-recognition capabilities of the interlocked receptor, giving unusual iodide selectivity in a competitive aqueous medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
192
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 254 publications
(200 citation statements)
references
References 26 publications
5
192
0
3
Order By: Relevance
“…However, in the past few years, a number of studies have demonstrated that XB anion receptors exhibit superior and contrasting recognition properties in comparison to their hydrogen‐bonding (HB) analogues 26. 27 For instance, we very recently reported that XB is remarkably effective for halide‐anion binding in water, and results in significantly enhanced recognition in acyclic and rotaxane‐based receptors compared to the analogous hydrogen‐bonding systems 28…”
Section: Introductionmentioning
confidence: 99%
“…However, in the past few years, a number of studies have demonstrated that XB anion receptors exhibit superior and contrasting recognition properties in comparison to their hydrogen‐bonding (HB) analogues 26. 27 For instance, we very recently reported that XB is remarkably effective for halide‐anion binding in water, and results in significantly enhanced recognition in acyclic and rotaxane‐based receptors compared to the analogous hydrogen‐bonding systems 28…”
Section: Introductionmentioning
confidence: 99%
“…5 Many of these have shown enhanced binding properties over their hydrogen bonding (HB) analogues. 6,7 The electron-deficient 8 1,2,3-triazole motif has been exploited for anion recognition as an effective C-H hydrogen bond donor when integrated into multidentate macrocycles 9 and acyclic foldamers. [10][11][12] While the related 5-iodotriazole unit has been used as XB donor for anion binding, such XB anion hosts are rare in the literature.…”
mentioning
confidence: 99%
“…Subsequently, a large number of MIMs have been prepared (Vickers & Beer 2007) using a range of anions as templates, including Cl − , Br − and SO 2− 4 , and most recently of all, the templation of MIMs involving halide anions has been invigorated by the newly discovered concept of halogen bonding (Kilah et al 2010). The development of functional devices, for example optical chloride sensors (Gassensmith et al 2010) based on anion-templated MIMs, underscores their potential for applications in the future.…”
Section: Synthetic Approaches To Mechanically Interlocked Moleculesmentioning
confidence: 99%